The Effect of Locus in Control Teaching Strategy on Students Speaking Skills at Smp Negeri 7 Lawe Sigala-Gala - Zai, Forester; Tampubolon, Sahlan; Silitonga, Harpen (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to determine the types of errors found in students' speaking skills. Knowing the dominant errors of students when speaking English to see its effect on speaking skills. There is a phenomenon in this study that almost every student struggles with past tense errors when learning English. To achieve the objectives of this study, the researcher used a quantitative research design. The population of all eighth-grade students of SMP Negeri 7 Lawe Sigala-gala and the sample of this study amounted to 20 students. The data collection technique used by the researcher was a test. To analyze the data involves four steps, namely: identifying errors, describing errors, and summarizing data findings. Based on the findings of this study, the author found that there were 87 (36%) speaking errors, 39 (19%) content errors, 45 (21%) language errors, 45 (21%) vocabulary errors, 8 (3%) mechanical errors. Eighth grade students at SMP Pamen made several errors in the categories listed above. Based on the data, students learn about the elements that contribute to students' errors in speaking English. They struggle with grammatical parts in the text and the overall structure and arrangement that they do not understand, including problems that they do not understand when performing speaking, etc.